2005
DOI: 10.1038/sj.ejcn.1602352
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in serum levels of trace elements in tuberculosis and HIV infections

Abstract: Objective: To evaluate serum concentrations of trace elements in tuberculosis (TB) patients with or with out human immunodeficiency virus (HIV) coinfection before and after anti-TB chemotherapy. Subjects: A total of 155 TB patients, 74 of which were coinfected with HIV, and 31 healthy controls from Gondar, Ethiopia. Methods: Serum levels of copper, zinc, selenium and iron were determined using an inductively coupled plasma mass spectrometer from all subjects at baseline and from 44 TB patients (22 with HIV coi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
64
5
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(83 citation statements)
references
References 45 publications
(46 reference statements)
7
64
5
1
Order By: Relevance
“…Other Ethiopian based studies have also shown a higher result. A study conducted in Gondar, 65.4 % [16] and Sidama, 77.9 % [15] revealed higher prevalence of undernutrition among adult tuberculosis patients compared to this study. This may be attributed to the difference in study context (urban dweller TB patients) and in socio-economic status of the society in those areas.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other Ethiopian based studies have also shown a higher result. A study conducted in Gondar, 65.4 % [16] and Sidama, 77.9 % [15] revealed higher prevalence of undernutrition among adult tuberculosis patients compared to this study. This may be attributed to the difference in study context (urban dweller TB patients) and in socio-economic status of the society in those areas.…”
Section: Discussionmentioning
confidence: 99%
“…A study in Gondar showed that the prevalence of undernutrition in adult TB patients co-infected with HIV was 71.6 %, which is higher when compared with the finding of this study 25.9 %. This could be due to the fact that the study in Gondar has included high number of TB/HIV co-infected patients who were more exposed to undernutrition because of double burden [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tuberculosis patients had a high level of copper and copper/zinc ratio when compared to healthy controls, and the alteration was more pronounced in those coinfected with HIV 27 .…”
Section: Discussionmentioning
confidence: 99%
“…Top on the list are those micronutrients that are involved in immune functions and antioxidant system. 7,[8][9][10] Antioxidant vitamins such as vitamins C and E often present a negative correlation between normal and individuals suffering from pathogenic infections. The levels of these parameters in subjects undergoing HAART therapy will serve as an indicator to determine its effectiveness.…”
mentioning
confidence: 99%